Infrared spectroscopy depth profiling of organic thin films. Issue 5 (5th March 2021) - Yu, Jinde; Xing, Yifan; Shen, Zichao; Zhu, Yuanwei; Neher, Dieter; Koch, Norbert; Lu, Guanghao
Abstract : FDD-IR spectra combined with soft plasma etching is introduced to study organic film property along film-depth. It provides insights into different kinds of organic films, all equipment and methodology are easily accessible in laboratories worldwide. Abstract : Organic thin films are widely used in organic electronics and coatings. Such films often feature film-depth dependent variations of composition and optoelectronic properties. State-of-the-art depth profiling methods such as mass spectroscopy and photoelectron spectroscopy rely on non-intrinsic species (vaporized ions, etching-induced surface defects), which are chemically and functionally different from the original materials. Here we introduce an easily-accessible and generally applicable depth profiling method: film-depth-dependent infrared (FDD-IR) spectroscopy profilometry based on directly measuring the intrinsic material after incremental surface-selective etching by a soft plasma, to study the material variations along the surface-normal direction. This depth profiling uses characteristic vibrational signatures of the involved compounds, and can be used for both conjugated and non-conjugated, neutral and ionic materials. A film-depth resolution of one nanometer is achieved. We demonstrate the application of this method for investigation of device-relevant thin films, including organic field-effect transistors and organic photovoltaic cells, as well as ionized dopant distributions in doped semiconductors.